The Brekov Roma - "the best in Czechoslovakia". Gypsyness as a structure of relations and logic of social mobility in the socialist era. - Ort, Jan (Romano džaniben, 2023)
This text enters the discussion on the way of understanding the references to "Gypsies" in historical sources, here specifically in the context of socialist Czechoslovakia. In doing so, it goes beyond tracing the ways in which the state categorized the population, where many authors have already pointed to the official definition of "Gypsy" as a category of social deviance rather than ethnic (self-)identification. In an ethnographically informed approach to researching Romani histories, this text traces various overlapping contemporary discourses of ’gypsyness` and their negotiation within a locally anchored hierarchy of socio-economic relations. Using the case study of the eastern Slovakian village of Brekov, it specifically traces how this category spoke not only to the exclusion of Roma from non-Romani society, but also to the ways in which relations between Roma themselves were defined, not only at the narrative level, but also at the level of concrete social practice. In so doing, it is a contribution to the growing debate among historians and Romani studies scholars about the nature of agency of the Roma in history.